IMPAK PSIKOLOGI GURU HASIL KEPEMIMPINAN PENGETUA (Sains Humanika, 2008)
Educational scholars especially in the area of educational leadership believe that school administrators and principals are the most important individuals in motivating and producing highly committed teachers in schools. In relation to this issue, this research was conducted to determine the psychological impacts (trust and commitment) of teachers as a result of principals’ leadership orientations. Respondents for this study were 200 teachers in two secondary schools in Batu Pahat, Johore. Findings showed that the level of trust among teachers towards the principals were at the average level while teachers’ commitment towards schools were ranked as high. This findings revealed evidences that school principals were the most trusted individuals in leading schools according to teachers’ perceptions. The results also proved that principals leadership orientations were potrayed as the significant preditor towards teachers’ commitment and levels of trust in school.
Keywords: Trust; commitment; teachers; principals; leadership orientations